2012
DOI: 10.1371/journal.pone.0052415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interleukin 6 Deficiency on Renal Interstitial Fibrosis

Abstract: Our recent studies have shown that bone marrow-derived fibroblast precursors contribute significantly to the pathogenesis of renal fibrosis. However, the molecular mechanisms underlying the recruitment and activation of bone marrow-derived fibroblast precursors are incompletely understood. We found that interleukin 6 was induced in the kidney in a murine model of renal fibrosis induced by unilateral ureteral obstruction. Therefore, we investigated if interleukin 6 play a role in the recruitment and maturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…CD45 and CD206 are the markers of hematopoietic cells, and PDGFR-β is a mesenchymal marker. A previous study showed that bone marrow-derived fibroblasts contributed significantly to the development of renal fibrosis [41]. In the present study, we showed that PTEN activity had a pathologically important effect on recruiting myeloid fibroblasts into the kidney and proliferation of interstitial fibroblasts in the kidney during renal fibrosis.…”
Section: Discussionsupporting
confidence: 63%
“…CD45 and CD206 are the markers of hematopoietic cells, and PDGFR-β is a mesenchymal marker. A previous study showed that bone marrow-derived fibroblasts contributed significantly to the development of renal fibrosis [41]. In the present study, we showed that PTEN activity had a pathologically important effect on recruiting myeloid fibroblasts into the kidney and proliferation of interstitial fibroblasts in the kidney during renal fibrosis.…”
Section: Discussionsupporting
confidence: 63%
“…For UUO model, male WT and IL-4Rα KO mice were anesthetized by intraperitoneal injection of ketamine and xylazine. Through a flank incision, the left ureter was exposed and completely ligated using fine suture material (4-0 silk) at two points as described 9, 13, 14, 4244 .…”
Section: Methodsmentioning
confidence: 99%
“…The UUO procedure was performed as described. 6,7,17,42,43 Bone Marrow Transplantation Bone marrow transplantation was performed as previously described. 6,10,17,42,44 Briefly, bone marrow cells (5310 6 ) from WT or STAT6 KO mice were transferred to lethally irradiated WT mice.…”
Section: Animals and Uuo Surgerymentioning
confidence: 99%